Composition for electrolyte, electrolyte, preparation method of electrolyte and lithium ion battery
By using specific compositions in the electrolyte, including lithium salts, film-forming additives, organic solvents and additives, the problems of slow ion conduction of single-particle graphite negative electrodes and poor wetting properties of the electrolyte are solved, and the rate performance and circulation performance of lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411797220.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the ion conduction of a single-particle graphite negative electrode is slow, and the electrolyte is poor in wetting, resulting in poor battery magnification and lithium degradation of the negative electrode.
A composition for electrolyte is provided, which contains lithium salt, film forming additive, organic solvent and additive, wherein the lithium salt content is 25-35 wt%, the film forming additive content is 25-30 wt%, the organic solvent content is 30-42 wt%, and the additive content is 2-10 wt%, and the components are contacted and mixed under a protective atmosphere to prepare an electrolyte.
Significantly improve the electrolyte infiltration characteristics on the surface of single-particle graphite negative electrode, improve the electrolyte replenishment rate, reduce the interface impedance of the electrode/electrolyte, improve the rate performance of lithium-ion batteries, reduce battery polarization, and improve cycle performance.
Smart Images

Figure CN119764553A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte composition, an electrolyte and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In order to promote the application of renewable energy such as wind power and photovoltaic power, it has become a trend to equip electrochemical energy storage devices represented by lithium iron phosphate batteries. In order to improve the operating life of lithium iron phosphate battery energy storage systems, the use of single-grain graphite negative electrodes with smaller specific surface area is the current mainstream strategy. However, due to the large particle size of single-grain graphite, ion conduction is more difficult during high-rate operation, resulting in reduced battery energy efficiency and poor rate performance. When the compaction density of the pole piece increases, the pores inside the electrode decrease, and the electrolyte infiltration becomes difficult, which will further lead to difficulties in ion conduction and aggravate the above problems.
[0003] The commercial electrolytes commonly used are mainly composed of lithium hexafluorophosphate and carbonate solvents. The surface tension of the electrolyte is high, and the wettability on the single-grain graphite negative electrode is poor, which makes it difficult to meet the ion conduction requirements of the electrode under high-rate operation. In addition, the interface impedance formed by the conventional commercial electrolyte on the surface of the graphite negative electrode is high, which will further lead to the deterioration of the electrode rate performance. Therefore, it is urgent to develop a single-grain graphite negative electrode high-rate electrolyte with low surface tension and the ability to form a low-impedance interface.
[0004] CN117832630A discloses an electrolyte compatible with a lithium iron manganese phosphate battery and a lithium battery, wherein the electrolyte includes a lithium salt, an organic solvent and an additive; wherein the lithium salt includes: lithium bis(fluorosulfonyl)imide salt and lithium hexafluorophosphate; the organic solvent includes: ethylene carbonate, ethyl methyl carbonate and diethyl carbonate; the additive includes: vinylene carbonate, 1,3-propane sultone, vinyl sulfate, lithium difluorophosphate and tris(trimethylsilyl)phosphate. This technical solution has a good effect on interface improvement, gas production inhibition and cycle optimization, but it still has the defects of insufficient electrolyte wettability and failure to meet the high rate requirements of the battery. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the prior art of slow ion conduction of single-grain graphite negative electrodes and poor electrolyte wettability, which lead to poor battery rate performance and negative electrode lithium deposition.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for an electrolyte, wherein the composition contains a lithium salt, a film-forming additive, an organic solvent and an auxiliary agent;
[0007] Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 25-35wt%, the content of the film-forming additive is 25-30wt%, the content of the organic solvent is 30-42wt%, and the content of the auxiliary agent is 2-10wt%;
[0008] The auxiliary agent is N-methyl-N-(trifluoromethylthio)aniline.
[0009] Preferably, based on the total weight of the electrolyte, the content of the lithium salt is 29-30wt%, the content of the film-forming additive is 29-30wt%, the content of the organic solvent is 35-40wt%, and the content of the auxiliary agent is 2-5wt%.
[0010] Preferably, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and further includes at least two of lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.
[0011] Preferably, the lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate) borohydride and lithium nitrate in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.5; or
[0012] The lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate and lithium bis(oxalatoborate) in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.5.
[0013] Preferably, the film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile and methylene methanedisulfonate.
[0014] Preferably, the film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3,6-hexanetrinitrile in a mass ratio of 1:1-3:0.5-1.5:0.5-1.5; or
[0015] The film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3-propane sultone in a mass ratio of 1:1-3:0.5-1.5:0.5-1.5.
[0016] Preferably, the organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0017] The second aspect of the present invention provides a method for preparing an electrolyte, the method comprising: contacting and mixing the components in the electrolyte composition described in the first aspect under a protective atmosphere to obtain an electrolyte.
[0018] The third aspect of the present invention provides an electrolyte prepared by the method described in the second aspect.
[0019] A fourth aspect of the present invention provides a lithium ion battery, the battery comprising: a positive electrode, a negative electrode, a separator and an electrolyte;
[0020] The electrolyte is the electrolyte described in the third aspect.
[0021] Through the above technical solution, the present invention has at least the following advantages:
[0022] The electrolyte prepared from the electrolyte composition provided by the present invention can significantly improve the electrolyte wetting characteristics of the surface of a single-grain graphite negative electrode, increase its electrolyte replenishment rate during the cycle, and reduce the interface impedance of the electrode / electrolyte; applying the electrolyte to a lithium-ion battery system using a single-grain graphite negative electrode can significantly improve its rate performance, reduce battery polarization, and improve cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a contact angle test diagram of the electrolyte prepared in Example 1 of the present invention;
[0024] Figure 2 This is the rate test charge-discharge curve obtained in Example 1 of the present invention;
[0025] Figure 3 This is the rate test charge-discharge curve obtained in Example 1 of the present invention;
[0026] Figure 4 This is a cycle performance test diagram obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] As mentioned above, the first aspect of the present invention provides a composition for an electrolyte, the composition comprising a lithium salt, a film-forming additive, an organic solvent and an auxiliary agent;
[0029] Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 25-35wt%, the content of the film-forming additive is 25-30wt%, the content of the organic solvent is 30-42wt%, and the content of the auxiliary agent is 2-10wt%;
[0030] The auxiliary agent is N-methyl-N-(trifluoromethylthio)aniline.
[0031] The inventors of the present invention discovered during the research process that when N-methyl-N-(trifluoromethylthio)aniline is added as an auxiliary agent in the electrolyte composition, the rate performance of the single-grain graphite negative electrode can be improved. This may be because the surface activity of its fluorinated group greatly reduces the surface tension of the electrolyte, and the fluorine and nitrogen elements contained therein can also participate in the formation of the SEI film at the negative electrode interface, thereby enhancing the ion conductivity of the negative electrode interface and reducing the interface impedance, thereby achieving the ultimate purpose of improving the rate performance of the single-grain graphite negative electrode.
[0032] Preferably, based on the total weight of the electrolyte, the content of the lithium salt is 29-30wt%, the content of the film-forming additive is 29-30wt%, the content of the organic solvent is 35-40wt%, and the content of the auxiliary agent is 2-5wt%. The inventors of the present invention have found that in this preferred case, the high-rate charge and discharge capacity of the lithium-ion battery can be further significantly improved.
[0033] Preferably, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and further includes at least two of lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.
[0034] Preferably, the lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate) borohydride and lithium nitrate in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.5; or
[0035] The lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate and lithium bis(oxalatoborate) in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.5.
[0036] The inventors of the present invention have found that, under the above preferred conditions, the high-rate charge and discharge capacity of the lithium-ion battery can be further improved.
[0037] Preferably, the film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile and methylene methanedisulfonate.
[0038] Preferably, the film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3,6-hexanetrinitrile in a mass ratio of 1:1-3:0.5-1.5:0.5-1.5; or
[0039] The film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3-propane sultone in a mass ratio of 1:1-3:0.5-1.5:0.5-1.5.
[0040] In the above preferred case, the wettability of the electrolyte can be further improved, and the charge and discharge polarization of the lithium-ion battery can be lowered, thereby further improving the rate performance of the lithium-ion battery.
[0041] Preferably, the organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, more preferably a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1-1.6.
[0042] As mentioned above, the second aspect of the present invention provides a method for preparing an electrolyte, which comprises: contacting and mixing the components in the electrolyte composition described in the first aspect under a protective atmosphere to obtain an electrolyte.
[0043] Preferably, the protective atmosphere is selected from at least one of nitrogen, argon and helium.
[0044] More preferably, in the protective atmosphere, the contents of water and oxygen are each independently less than 0.1 ppm.
[0045] It should be noted that the present invention has no specific requirements on the time and temperature of the contact mixing, and the conditions known in the art can be adopted. According to a particularly preferred embodiment, the contact mixing conditions include: a temperature of 10-30°C and a time of 6-24h.
[0046] As mentioned above, the third aspect of the present invention provides an electrolyte prepared by the method described in the second aspect.
[0047] As mentioned above, the fourth aspect of the present invention provides a lithium ion battery, the battery comprising: a positive electrode, a negative electrode, a separator and an electrolyte;
[0048] The electrolyte is the electrolyte described in the third aspect.
[0049] Preferably, the positive electrode is a lithium iron phosphate electrode sheet, the negative electrode is a single-grain graphite electrode sheet, and the separator is a polyolefin separator.
[0050] It should be noted that the present invention has no special requirements on the content of the electrolyte in the battery, and any content known in the art may be used.
[0051] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are commercially available products.
[0052] Lithium hexafluorophosphate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0053] Lithium bis(fluorosulfonyl)imide was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0054] Lithium borofluoride oxalate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0055] Lithium nitrate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0056] Fluoroethylene carbonate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0057] Vinylene carbonate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0058] Ethylene sulfate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0059] Hexane trinitrile was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0060] Ethylene carbonate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0061] Dimethyl carbonate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0062] Ethyl methyl carbonate was purchased from Suzhou Duoduo Chemical Technology Co., Ltd.;
[0063] N-methyl-N-(trifluoromethylthio)aniline, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No. 66476-44-6;
[0064] Lithium metal flakes were purchased from Tianjin Zhongneng Lithium Industry Co., Ltd. with a purity of 99.9%;
[0065] The single-grain graphite negative electrode was purchased from Shenzhen Kejing Zhida Technology Co., Ltd. with a CAS number of 7782-42-5.
[0066] In the following examples, room temperature refers to a temperature of 23±2°C.
[0067] In the following examples, lithium salt I is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate) borohydride, and lithium nitrate in a mass ratio of 1:1:1:1;
[0068] Lithium salt II is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate and lithium bis(oxalatoborate) in a mass ratio of 1:1:1:1;
[0069] The lithium salt III is a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 1:1;
[0070] Film-forming additive I is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3,6-hexanetrinitrile in a mass ratio of 1:2:1:1;
[0071] Film-forming additive II is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3-propane sultone in a mass ratio of 1:2:1:1;
[0072] The film-forming additive III is a combination of fluoroethylene carbonate and vinylene carbonate in a mass ratio of 1:1;
[0073] The organic solvent I is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1.32;
[0074] The organic solvent II is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1.08;
[0075] The organic solvent III is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1.4;
[0076] The organic solvent IV is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1.52;
[0077] Auxiliary agent I is N-methyl-N-(trifluoromethylthio)aniline;
[0078] Auxiliary agent II is fluorobenzene.
[0079] Example 1
[0080] In an argon-protected glove box (H2O and O2 contents were both less than 0.1 ppm), lithium salt, film-forming additive, organic solvent, and auxiliary agent were contacted and mixed (temperature was 25°C, time was 6 h), and stirred at room temperature for 24 h to obtain an electrolyte.
[0081] The specific types and amounts of raw materials in Example 1 are shown in Table 1. Unless otherwise specified, the other examples are carried out using the same process as Example 1, except for the raw materials and ratios used, as shown in Table 1.
[0082] Table 1
[0083]
[0084] Comparative Example 3
[0085] This comparative example is carried out in a similar manner to Example 1, except that in this comparative example, the amount of lithium salt is adjusted to 1.25 g, the amount of film-forming additive is adjusted to 0.5 g, the amount of organic solvent is adjusted to 8.05 g, and the amount of auxiliary agent is adjusted to 0.2 g to obtain an electrolyte.
[0086] Comparative Example 4
[0087] This comparative example is carried out in a similar manner to Example 1, except that the auxiliary agent I in Example 1 is replaced by an auxiliary agent II of equal mass to obtain an electrolyte.
[0088] Test Case
[0089] The surface contact angle of the electrolyte prepared in the test example was tested, and a button-type half-cell was assembled using the electrolyte prepared in the example to test its rate performance and cycle performance.
[0090] The specific test methods are:
[0091] (1) A single-grain graphite negative electrode was used as the substrate, and the contact angle of the electrolyte on its surface was tested using a contact angle tester of model DSA100.
[0092] (2) A single-grain graphite negative electrode is used as the working electrode, and a metal lithium sheet is used as the counter electrode. The specific assembly sequence is: positive electrode shell-graphite electrode sheet-electrolyte-diaphragm-electrolyte-metal lithium sheet-gasket-spring-negative electrode shell; after the assembly is completed, the button half-cell is tested for its discharge capacity at 0.1C, 0.5C, 1C, 3C, and 5C rates, and its discharge capacity after 100 cycles is tested at a 1C rate.
[0093] The test results are shown in Table 2.
[0094] Table 2
[0095]
[0096]
[0097] The present invention is exemplified in Figure 1 A contact angle test diagram of the electrolyte prepared in Example 1 is provided; and Figure 2 The contact angle test diagram of the electrolyte of Comparative Example 1 is provided in Table 2. Figure 1 , Figure 2 It can be seen from the results that the electrolyte prepared by the present invention can significantly improve the electrolyte wetting characteristics of the surface of the single-grain graphite negative electrode, thereby significantly improving the rate performance of the battery.
[0098] The present invention is exemplified in Figure 3 The rate test charge-discharge curve of the electrolyte prepared in Example 1 is provided; Figure 3 The results show that the electrolyte prepared by the present invention can significantly reduce the polarization of the battery, and there is no obvious polarization increase with the increase of the rate.
[0099] The present invention is exemplified in Figure 4The cycle performance test diagram of the electrolyte prepared in Example 1 is provided; Figure 4 The results show that the electrolyte prepared by the present invention can ensure the long-term stable cycle of the battery.
[0100] It can be seen from the above results that the electrolyte prepared from the electrolyte composition provided by the present invention has a smaller contact angle on the surface of a single-grain graphite negative electrode, a higher rate discharge specific capacity and a higher cycle discharge specific capacity than the control example, and can significantly improve the performance of a single-grain graphite negative electrode in rate cycling.
[0101] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composition for an electrolyte, characterized in that: The composition contains lithium salt, film-forming additive, organic solvent and auxiliary agent; Wherein, based on the total weight of the electrolyte, the content of the lithium salt is 25-35wt%, the content of the film-forming additive is 25-30wt%, the content of the organic solvent is 30-42wt%, and the content of the auxiliary agent is 2-10wt%; The auxiliary agent is N-methyl-N-(trifluoromethylthio)aniline.
2. The composition according to claim 1, wherein Based on the total weight of the electrolyte, the content of the lithium salt is 29-30wt%, the content of the film-forming additive is 29-30wt%, the content of the organic solvent is 35-40wt%, and the content of the auxiliary agent is 2-5wt%.
3. The composition according to claim 1 or 2, wherein The lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and further includes at least two of lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate) and lithium nitrate.
4. The composition according to claim 3, wherein The lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalate) borohydride and lithium nitrate in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.5; or The lithium salt is a combination of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate and lithium bis(oxalatoborate) in a mass ratio of 1:0.5-1.5:0.5-1.5:0.5-1.
5.
5. The composition according to claim 1 or 2, wherein The film-forming additive is selected from at least three of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3,6-hexanetrinitrile and methylene methanedisulfonate.
6. The composition according to claim 5, wherein The film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3,6-hexanetrinitrile in a mass ratio of 1:1-3:0.5-1.5:0.5-1.5; or The film-forming additive is a combination of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate and 1,3-propane sultone in a mass ratio of 1:1-3:0.5-1.5:0.5-1.
5.
7. The composition according to claim 1 or 2, wherein The organic solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
8. A method for preparing an electrolyte, characterized in that: The method comprises: contacting and mixing the components in the electrolyte composition according to any one of claims 1 to 7 under a protective atmosphere to obtain an electrolyte.
9. The electrolyte prepared by the method according to claim 8.
10. A lithium ion battery, characterized in that: The battery comprises: a positive electrode, a negative electrode, a separator and an electrolyte; The electrolyte is the electrolyte according to claim 9.
Citation Information
Patent Citations
Adaptive electrolyte of lithium iron manganese phosphate battery and lithium battery
CN117832630A